The Effectiveness of Hazelnut Cultivars and Genotypes on Sensory, Physical, and Chemical Properties of Chocolate Cream - Babak Maleki; Mahsa Tabari; Alireza Eslami; Behzad Kaviani (Journal of Nuts)
Chocolate is made from roasted and ground cocoa seeds and used on its own or as a flavoring to prepare various desserts. The high price of cocoa butter and the need for tempering operations have reduced the desire of chocolate manufacturers to use this product. As a result, high-quality, lower-priced substitutes for cocoa butter are increasingly being used in the preparation of chocolate. Hazelnut (Corylus avellana L.) is one of the most commonly used nuts as an additive in the preparation of sweets and chocolates, and its cultivation has increased in recent decades. In the present study, the paste of two varieties (Round de Peymon and Segrob hazelnuts) and two genotypes (Eshkevar 1 and Eshkevar 3 hazelnuts) of hazelnut was used instead of cocoa cream to prepare chocolate cream. After the preparation of this cream, its physicochemical (fat, protein, peroxide, sugar, moisture, acidity, ash, and viscosity) and sensory (color, taste, odor, texture, and overall acceptability) properties were evaluated. The results showed that the highest protein content, the lowest moisture content, and the highest overall acceptability were associated with Eshkevar 3 hazelnut. In conclusion, this variety is a promising approach for producing chocolate cream with reasonable quality and price. The cultivation of this hazelnut genotype is recommended to gardeners and growers.